Sectoral specificities of flexible working arrangements - Pintassilgo, Ana Catarina De Almeida (2021)
We study gender heterogeneity in use and access to flexible working hours in the Portuguese labour market, using a fixed effects approach. We combine linked employee-employer data, the labour force survey, and our own collect and coded litigation database, covering the periods from 2013 to 2019. We show that female workers have considerably lower use and access to flexitime, even in establishments able to provide it and in female dominated sectors. Our preferred estimate suggests that being a woman reduces the probability of having a flexible schedule by 7.3%. For female dominated sectors - education, and health and social care- the magnitude is even larger: 15.2% and 16.5%. Additionally, we provide evidence on therole of collective bargaining power in fostering female access to flexitime.